2019
DOI: 10.1186/s12879-019-3966-7
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis infection risk, preventive therapy care cascade and incidence of tuberculosis disease in healthcare workers at Maputo Central Hospital

Abstract: Background Mozambican healthcare workers have high rates of latent and active tuberculosis, but occupational screening for tuberculosis is not routine in this setting. Furthermore, the specificity of tuberculin skin testing in this population compared with interferon gamma release assay testing has not been established. Methods This study was conducted among healthcare workers at Maputo Central Hospital, a public teaching quaternary care hospital in Mozambique. With a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…Mozambique lacks nationally representative data on TB rates among health workers [ 8 , 9 , 10 ]. However, a recent study conducted at Maputo Central Hospital, a public teaching quaternary care hospital, identified an annual incidence rate among health workers of 1676 per 100,000, consistent with the median incidence rate of 1180 per 100,000 reported in a meta-analysis of active TB among health workers in high-TB incidence countries [ 11 ]. Effective implementation of a workplace TB policy for health workers is thus urgently needed in Mozambique [ 11 , 12 , 13 ].…”
Section: Introductionsupporting
confidence: 64%
“…Mozambique lacks nationally representative data on TB rates among health workers [ 8 , 9 , 10 ]. However, a recent study conducted at Maputo Central Hospital, a public teaching quaternary care hospital, identified an annual incidence rate among health workers of 1676 per 100,000, consistent with the median incidence rate of 1180 per 100,000 reported in a meta-analysis of active TB among health workers in high-TB incidence countries [ 11 ]. Effective implementation of a workplace TB policy for health workers is thus urgently needed in Mozambique [ 11 , 12 , 13 ].…”
Section: Introductionsupporting
confidence: 64%
“…Although a high number of TB exposures occurred, most were concentrated in specific units or departments, such as the ICU, the department of infectious diseases, or pulmonology. In previous studies that examined the mechanisms underlying exposure to TB and the risks to healthcare personnel with respect to developing LTBI [7,12,13], the prevalence of LTBI was high among HCWs working in situations with a higher inherent risk of TB exposure, such as working in high-risk departments or having a longer duration of working hours. Therefore, although it is difficult to confirm that the cases of LTBI identified in this study among HCWs was caused by exposure to the 222 patients included in the study, exposure to TB patients while working in a medical institution is likely.…”
Section: Discussionmentioning
confidence: 98%
“…TB healthcare workers (HCWs) are one of the populations most likely to develop LTBI, as they are those with frequent direct or indirect exposure to M. tuberculosis. Multiple studies have shown a significant correlation between TB infection and occupational exposure (Zhang et al, 2013;Shi et al, 2018;Graves et al, 2019). The prevalence of TB among nurses working in TB-related departments is 5.1 times higher than in the general population, and the incidence of LTBI among HCWs is 17-36% (Jo et al, 2008;Mok, 2016).…”
Section: Introductionmentioning
confidence: 99%